Laser aluminum foil

By molding the composite aluminum foil lining film and using environmentally friendly raw materials to prepare peelable adhesives, the problems of cumbersome processes and environmental pollution of traditional laser packaging materials are solved, and the environmental protection and aesthetics of laser aluminum foil are improved, and excellent UV photo-stripping is available. Effect.

CN119116484APending Publication Date: 2024-12-13NANCHANG GUANGQUN LASER TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411545346.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The production process of traditional laser packaging materials is cumbersome and expensive, and environmental pollution caused by the use of organic solvents, which violates the concept of green production.

Method used

The composite aluminum foil lining film is prepared by molding mechanism, and the peelable adhesive is used to mix and aged with photopolymerizable acrylate copolymer, photoinitiator and diluent, including environmentally friendly raw materials such as polyurethane acrylate prepolymer and castor oil to form UV photoinduced Peelable effect.

Benefits of technology

It has achieved improved environmental protection and aesthetics of laser aluminum foil, met VOC requirements, reduced the content of residual solvents and monomers, and has excellent UV photo-stripping effect, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a laser aluminum foil, and relates to the technical field of packaging materials. The laser aluminum foil is obtained by putting a composite aluminum foil lining film into a molding press for molding, the composite aluminum foil lining film comprises a base film layer, an aluminum foil layer and a peelable adhesive bonded between the base film layer and the aluminum foil layer. The peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by carrying out prepolymerization on a diisocyanate monomer, castor oil and 2-hydroxyethyl acrylate; the acrylic acid copolymer is obtained by copolymerizing 2-hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol triacrylate and acrylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the technical field of packaging materials, in particular to a laser aluminum foil. Background Art

[0004] As consumers' requirements for packaging aesthetics and environmental friendliness continue to increase, the market demand for packaging materials that can provide a unique visual experience and meet environmental standards is also gradually increasing. The traditional production process of laser packaging materials usually uses biaxially oriented polyester (BOPET) film as the base material, by applying a layer of resin on the surface of the film, and then using laser mold pressing technology to create a specific laser pattern on the resin layer. Next, vacuum aluminum plating technology is used to cover the laser pattern layer with a thin layer of aluminum film, thereby achieving the dual effects of beauty and moisture resistance. However, this method is not only cumbersome and costly, but also due to the widespread use of organic solvents, it leads to serious environmental problems such as VOCs (volatile organic compounds) emissions, which is contrary to the green production concept advocated today.

[0005] In view of the shortcomings of these traditional technologies, the present invention provides a laser aluminum foil. Summary of the invention

[0007] The purpose of the present invention is to provide a laser aluminum foil to solve the technical problems mentioned in the above background technology.

[0008] The technical solution for achieving the purpose of the present invention is:

[0009] A laser aluminum foil is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film comprises a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer, the peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator, and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate.

[0010] Furthermore, the preparation steps of the peelable adhesive are as follows: 100 parts by mass of a photopolymerizable acrylate copolymer, 1 to 1.5 parts by mass of a photoinitiator, and 1.5 to 2.5 parts by mass of a diluent are uniformly mixed, and aged at 58 to 62° C. for one day to obtain a peelable adhesive.

[0011] Furthermore, the preparation steps of the photopolymerizable acrylate copolymer are as follows: the acrylate copolymer is heat-treated at 78-82°C for 18-22 minutes, then mixed with a polyurethane acrylate prepolymer at a mass ratio of 1:0.8-1.2, and aged at 58-62°C for one day to obtain a photopolymerizable acrylate copolymer.

[0012] Furthermore, the preparation steps of the acrylate copolymer are as follows: under a nitrogen atmosphere, 14 to 18 parts by mass of 2-hydroxyethyl acrylate, 3 to 5 parts by mass of butyl acrylate, 1.6 to 1.8 parts by mass of methyl methacrylate, 2 to 2.2 parts by mass of pentaerythritol triacrylate, and 0.8 to 0.9 parts by mass of acrylic acid are mixed to form a monomer solution, and a 3% to 7% mass fraction of an initiator di-tert-butyl peroxide ethanol solution of 0.1 times the mass of the monomer solution is added, and the mixture is stirred and mixed uniformly to obtain a mixed solution; 30% of the mixed solution is added to a reactor, and the reactor is heated to 70°C under nitrogen protection, and the remaining mixed solution is then added dropwise to the reactor, and the dropping time is controlled to be 55 to 65 hours. After the dropping is completed, the temperature is stirred and maintained at 65 to 75°C, and the reaction is continued for 1.8 to 2.2 hours, and the ethanol is evaporated to obtain an acrylate copolymer.

[0013] Furthermore, the preparation steps of the polyurethane acrylate prepolymer are as follows:

[0014] (1) Under a nitrogen atmosphere, 10-14 parts by weight of lysine diisocyanate, 18-19 parts by weight of biomass polyol, 0.001-0.0014 parts by weight of dibutyltin dilaurate, and 0.0034-0.0038 parts by weight of polymerization inhibitor were added to a reactor, and the temperature was slowly raised to 38-42°C, and then raised to 58-62°C under stirring conditions, and the reaction was carried out for 5.5-6.5 hours to obtain a biomass polyurethane prepolymer;

[0015] (2) Under a nitrogen atmosphere, 2 to 2.2 parts by weight of 2-hydroxyethyl acrylate was added to the reaction vessel in step (1) and the reaction was continued for 3.5 to 4.5 hours to obtain a polyurethane acrylate prepolymer.

[0016] Furthermore, the polymerization inhibitor is trinonyl phosphite.

[0017] Furthermore, the biomass polyol is castor oil.

[0018] Furthermore, the diisocyanate monomer is lysine diisocyanate.

[0019] By adopting the above technical solution, the present invention has the following beneficial effects:

[0020] (1) The laser aluminum foil of the present invention is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film includes a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer; the peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator, and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate; the acrylic copolymer is obtained by copolymerizing 2-hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol triacrylate, and acrylic acid. The laser aluminum foil prepared by the present invention meets the VOC requirements, the residual solvent and the residual monomer do not exceed the standard, and does not contain phthalic plasticizers, and the UV light-induced peelable effect of the laser aluminum foil is good.

[0021] (2) The acrylic copolymer of the peelable adhesive of the present invention is obtained by copolymerization of pentaerythritol triacrylate. The three acrylate groups in pentaerythritol triacrylate form a stable three-dimensional network structure with other monomers during the copolymerization process, which not only strengthens the cohesion and adhesion of the product, allowing the aluminum foil layer and the base film layer to be tightly combined during the molding process, but also improves the heat resistance and solvent resistance of the adhesive, ensuring stability at high temperatures or when exposed to organic solvents; in addition, when irradiated with ultraviolet light, cross-linking reactions occur between pentaerythritol triacrylate molecules to form a three-dimensional network structure. This structural change not only leads to a significant shrinkage of the material volume, but also produces tiny pores between the adhesive and the surface of the adherend. The presence of these pores weakens the adhesion between the two, which is the so-called "debonding" phenomenon, weakening the interaction with the substrate to achieve a better UV light-induced peelable effect.

[0022] (3) Castor oil is a natural plant oil with a wide range of sources and rich in hydroxyl functional groups, which makes it an ideal raw material for preparing polyurethane acrylate prepolymers. In the present invention, castor oil reacts with diisocyanate monomers and 2-hydroxyethyl acrylate to generate polyurethane acrylate prepolymers, which are then used to prepare photopolymerizable acrylate copolymers in peelable adhesives. The main advantages of using castor oil as biomass polyols are its environmental friendliness and superior performance: as a renewable resource, the use of castor oil helps reduce dependence on fossil fuels and reduce the carbon footprint in the production process, which is in line with the principles of green chemistry and sustainable development; its long-chain fatty acid structure gives the final product good flexibility and durability, and its high hydroxyl value makes the reaction with isocyanate more complete, so that the formed polyurethane acrylate prepolymer has a higher crosslinking density, thereby improving the mechanical properties and chemical resistance of the adhesive. In addition, the adhesive containing castor oil derivatives can quickly form a crosslinking network under ultraviolet light, resulting in volume shrinkage and the generation of interface micropores, thereby effectively reducing the adhesion between the adhesive and the substrate, and achieving an excellent peelable effect.

[0023] (4) The diisocyanate monomer of the present invention adopts lysine diisocyanate, which is derived from natural amino acid and is a bio-based material. The use of this raw material helps to reduce dependence on petroleum-based raw materials and reduce environmental impact during the production process, which is in line with the concepts of green chemistry and sustainable development. The amino and carboxyl structures in the lysine molecule give the prepolymer better flexibility and elasticity, significantly improve the mechanical properties of the final product, and improve the impact resistance and tear resistance of the adhesive. In addition, the multi-functional characteristics of lysine diisocyanate help to form a tighter cross-linked network, thereby improving the strength and durability of the material. Under ultraviolet light irradiation, the adhesive containing lysine diisocyanate can quickly form a cross-linked network, resulting in volume shrinkage and the generation of interface micropores. The presence of these micropores weakens the adhesion between the adhesive and the substrate, achieving an excellent peelable effect. The special structure of lysine diisocyanate helps to form more cross-linking points during the cross-linking process, further enhancing this effect. DETAILED DESCRIPTION

[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0026] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0027] The raw materials of the embodiments and comparative examples of the present invention are as follows:

[0028] The base film layer is a commercially available BOPP film with a thickness of 16 μm to 20 μm;

[0029] The polyether polyol used was commercially available polyether polyol DL-2000.

[0030] (Example 1)

[0031] A laser aluminum foil is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film comprises a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer, the peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator, and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate.

[0032] The preparation steps of the peelable adhesive are as follows:

[0033] (1) Under a nitrogen atmosphere, 10 parts by weight of lysine diisocyanate, 18 parts by weight of castor oil, 0.001 parts by weight of dibutyltin dilaurate, and 0.0034 parts by weight of a polymerization inhibitor, trinonyl phosphite, were added to a reactor. The temperature was slowly raised to 38° C. and then to 58° C. under stirring, and the reaction was carried out for 5.5 hours to obtain a biomass polyurethane prepolymer.

[0034] (2) Under a nitrogen atmosphere, 2 parts by weight of 2-hydroxyethyl acrylate was added to the reaction vessel in step (1) and the reaction was continued for 3.5 hours to obtain a polyurethane acrylate prepolymer.

[0035] (3) Under a nitrogen atmosphere, 14 parts by mass of 2-hydroxyethyl acrylate, 3 parts by mass of butyl acrylate, 1.6 parts by mass of methyl methacrylate, 2 parts by mass of pentaerythritol triacrylate and 0.8 parts by mass of acrylic acid were mixed to prepare a monomer solution, and a 3% ethanol solution of di-tert-butyl peroxide initiator in an amount of 0.1 times the mass of the monomer solution was added, and the mixture was stirred and mixed uniformly to obtain a mixed solution; 30% of the mixed solution was added to a reactor, and the reactor was heated to 70°C under nitrogen protection, and the remaining mixed solution was added dropwise to the reactor, and the dropping time was controlled to be 55 hours. After the dropping was completed, the mixture was stirred and maintained at 65°C, and the reaction was continued for 1.8 hours, and the ethanol was evaporated to obtain an acrylate copolymer;

[0036] (4) heat-treating the acrylate copolymer at 78° C. for 18 min, then mixing it with the polyurethane acrylate prepolymer at a mass ratio of 1:0.8, and aging it at 58° C. for one day to obtain a photopolymerizable acrylate copolymer;

[0037] (5) 100 parts by weight of a photopolymerizable acrylate copolymer, 1 part by weight of a photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, and 1.5 parts by weight of a diluent trimethylolpropane triacrylate were mixed evenly, and aged at 58° C. for one day to obtain a peelable adhesive.

[0038] Example 2

[0039] A laser aluminum foil is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film comprises a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer, the peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator, and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate.

[0040] The preparation steps of the peelable adhesive are as follows:

[0041] (1) Under a nitrogen atmosphere, 12 parts by weight of lysine diisocyanate, 18.5 parts by weight of castor oil, 0.0012 parts by weight of dibutyltin dilaurate, and 0.0036 parts by weight of a polymerization inhibitor, trinonyl phosphite, were added to a reactor. The temperature was slowly raised to 40°C and then to 60°C under stirring, and the reaction was carried out for 6 hours to obtain a biomass polyurethane prepolymer.

[0042] (2) Under a nitrogen atmosphere, 2.1 parts by mass of 2-hydroxyethyl acrylate was added to the reaction kettle in step (1) and the reaction was continued for 4 hours to obtain a polyurethane acrylate prepolymer.

[0043] (3) Under a nitrogen atmosphere, 16 parts by mass of 2-hydroxyethyl acrylate, 4 parts by mass of butyl acrylate, 1.7 parts by mass of methyl methacrylate, 2.1 parts by mass of pentaerythritol triacrylate and 0.85 parts by mass of acrylic acid were mixed to prepare a monomer solution, and a 5% ethanol solution of di-tert-butyl peroxide initiator in an amount of 0.1 times the mass of the monomer solution was added, and the mixture was stirred and mixed uniformly to obtain a mixed solution; 30% of the mixed solution was added to a reactor, and the reactor was heated to 70°C under nitrogen protection, and the remaining mixed solution was then added dropwise to the reactor, and the dropping time was controlled to be 60 hours. After the dropping was completed, the mixture was stirred and maintained at 70°C, and the reaction was continued for 2 hours, and the ethanol was evaporated to obtain an acrylate copolymer;

[0044] (4) heat-treating the acrylate copolymer at 80° C. for 20 minutes, then mixing it with the polyurethane acrylate prepolymer in a mass ratio of 1:1, and aging it at 60° C. for one day to obtain a photopolymerizable acrylate copolymer;

[0045] (5) 100 parts by weight of a photopolymerizable acrylate copolymer, 1.3 parts by weight of a photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, and 2 parts by weight of a diluent trimethylolpropane triacrylate were mixed evenly, and aged at 60° C. for one day to obtain a peelable adhesive.

[0046] Example 3

[0047] A laser aluminum foil is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film comprises a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer, the peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator, and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate.

[0048] The preparation steps of the peelable adhesive are as follows:

[0049] (1) Under a nitrogen atmosphere, 14 parts by weight of lysine diisocyanate, 19 parts by weight of castor oil, 0.0014 parts by weight of dibutyltin dilaurate, and 0.0038 parts by weight of a polymerization inhibitor, trinonyl phosphite, were added to a reactor. The temperature was slowly raised to 42° C. and then to 62° C. under stirring, and the reaction was carried out for 6.5 hours to obtain a biomass polyurethane prepolymer.

[0050] (2) Under a nitrogen atmosphere, 2.2 parts by mass of 2-hydroxyethyl acrylate was added to the reaction kettle in step (1) and the reaction was continued for 4.5 hours to obtain a polyurethane acrylate prepolymer.

[0051] (3) Under a nitrogen atmosphere, 18 parts by mass of 2-hydroxyethyl acrylate, 5 parts by mass of butyl acrylate, 1.8 parts by mass of methyl methacrylate, 2.2 parts by mass of pentaerythritol triacrylate and 0.9 parts by mass of acrylic acid were mixed to prepare a monomer solution, and a 7% mass fraction of an initiator di-tert-butyl peroxide ethanol solution was added in an amount of 0.1 times the mass of the monomer solution, and the mixture was stirred and mixed to obtain a mixed solution; 30% of the mixed solution was added to a reactor, and the reactor was heated to 70°C under nitrogen protection, and the remaining mixed solution was added dropwise to the reactor, and the dropping time was controlled to be 65 hours. After the dropping was completed, the mixture was stirred and maintained at 75°C, and the reaction was continued for 2.2 hours, and the ethanol was evaporated to obtain an acrylate copolymer;

[0052] (4) heat-treating the acrylate copolymer at 82° C. for 22 min, then mixing it with the polyurethane acrylate prepolymer at a mass ratio of 1:1.2, and aging it at 62° C. for one day to obtain a photopolymerizable acrylate copolymer;

[0053] (5) 100 parts by weight of a photopolymerizable acrylate copolymer, 1.5 parts by weight of a photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, and 2.5 parts by weight of a diluent trimethylolpropane triacrylate were mixed evenly, and aged at 62° C. for one day to obtain a peelable adhesive.

[0054] Comparative Example 1

[0055] The difference between Comparative Example 1 and Example 2 is that the acrylate copolymer only uses 2-hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, and acrylic acid, and the remaining steps and components are the same as those of Example 2.

[0056] Comparative Example 2

[0057] The difference between Comparative Example 2 and Example 2 is that the biomass polyurethane prepolymer is obtained by prepolymerization of isophorone diisocyanate and castor oil, and the remaining steps and components are the same as those of Example 2.

[0058] Comparative Example 3

[0059] The difference between Comparative Example 3 and Example 2 is that the biomass polyurethane prepolymer is obtained by prepolymerizing lysine diisocyanate and polyether polyol, and the remaining steps and components are the same as those in Example 2.

[0060] Effect example

[0061] The following table shows the performance data of the laser aluminum foils obtained in Examples 1 to 3 and Comparative Examples 1 to 3:

[0062] Benzene test results 180° peel strength before light exposure (N / 25 mm) 180° peel strength after light exposure (N / 25 mm) Peelability Example 1 Not detected 21.9 0.5 Can be peeled off, no residual glue Example 2 Not detected 22.6 0.4 Can be peeled off, no residual glue Example 3 Not detected 22.4 0.5 Can be peeled off, no residual glue Comparative Example 1 Not detected 21.2 0.7 Can be peeled off, the residual adhesive area accounts for 4% of the total area Comparative Example 2 Not detected 20.6 0.8 Can be peeled off, no residual glue Comparative Example 3 Not detected 16.4 1.4 Can be peeled off, with residual glue, the residual glue area accounts for 8% of the total area

[0063] From the data comparison of the embodiment and the comparative example in the above table, it can be obtained that the laser aluminum foil prepared in the embodiment meets the VOC requirements, the residual solvent and the residual monomer do not exceed the standard, and does not contain phthalate plasticizers, and the UV photo-induced stripping effect of the laser aluminum foil is good.

[0064] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A laser aluminum foil is obtained by placing a composite aluminum foil liner film into a molding machine for molding; the composite aluminum foil liner film comprises a base film layer, an aluminum foil layer, and a peelable adhesive bonded between the base film layer and the aluminum foil layer, characterized in that: The peelable adhesive is obtained by mixing and aging a photopolymerizable acrylate copolymer, a photoinitiator and a diluent; the photopolymerizable acrylate copolymer is obtained by mixing and aging a polyurethane acrylate prepolymer and an acrylic copolymer; the polyurethane acrylate prepolymer is obtained by prepolymerizing a diisocyanate monomer with castor oil and 2-hydroxyethyl acrylate.

2. The laser aluminum foil according to claim 1, characterized in that: The preparation steps of the peelable adhesive are as follows: 100 parts by weight of a photopolymerizable acrylate copolymer, 1 to 1.5 parts by weight of a photoinitiator, and 1.5 to 2.5 parts by weight of a diluent are uniformly mixed, and aged at 58 to 62° C. for one day to obtain the peelable adhesive.

3. The laser aluminum foil according to claim 2, characterized in that: The preparation steps of the photopolymerizable acrylate copolymer are as follows: the acrylate copolymer is heat-treated at 78-82° C. for 18-22 minutes, then mixed with a polyurethane acrylate prepolymer at a mass ratio of 1:0.8-1.2, and aged at 58-62° C. for one day to obtain the photopolymerizable acrylate copolymer.

4. The laser aluminum foil according to claim 3, characterized in that: The preparation steps of the acrylic ester copolymer are as follows: under a nitrogen atmosphere, 14-18 parts by mass of 2-hydroxyethyl acrylate, 3-5 parts by mass of butyl acrylate, 1.6-1.8 parts by mass of methyl methacrylate, 2-2.2 parts by mass of pentaerythritol triacrylate, and 0.8-0.9 parts by mass of acrylic acid are mixed to form a monomer solution, 0.1 times the mass of the monomer solution and a mass fraction of 3%-7% of an initiator di-tert-butyl peroxide ethanol solution are added, and the mixture is stirred and mixed uniformly to obtain a mixed solution; 30% of the mixed solution is added to a reactor, and the reactor is heated to 70° C. under nitrogen protection, and the remaining mixed solution is dripped into the reactor, and the dripping time is controlled to be 55-65 hours. After the dripping is completed, the temperature is stirred and maintained at 65-75° C., and the reaction is continued for 1.8-2.2 hours, and the ethanol is evaporated to obtain an acrylic ester copolymer.

5. The laser aluminum foil according to claim 3, characterized in that: The preparation steps of the polyurethane acrylate prepolymer are as follows: (1) Under a nitrogen atmosphere, 10-14 parts by weight of lysine diisocyanate, 18-19 parts by weight of biomass polyol, 0.001-0.0014 parts by weight of dibutyltin dilaurate, and 0.0034-0.0038 parts by weight of polymerization inhibitor were added to a reactor, and the temperature was slowly raised to 38-42°C, and then raised to 58-62°C under stirring conditions, and the reaction was carried out for 5.5-6.5 hours to obtain a biomass polyurethane prepolymer; (2) Under a nitrogen atmosphere, 2 to 2.2 parts by weight of 2-hydroxyethyl acrylate was added to the reaction vessel in step (1) and the reaction was continued for 3.5 to 4.5 hours to obtain a polyurethane acrylate prepolymer.

6. The laser aluminum foil according to claim 1, characterized in that: The polymerization inhibitor is trinonyl phosphite.

7. The laser aluminum foil according to claim 1, characterized in that: The biomass polyol adopts castor oil.

8. The laser aluminum foil according to claim 7, characterized in that: The diisocyanate monomer is lysine diisocyanate.

Citation Information

Patent Citations

  • Polyurethane adhesive with degradation features and preparation method thereof

    CN109810666A

  • Preparation method of castor oil-based fully-crosslinked UV (Ultraviolet) photoinduced peelable glue for silicon wafer cutting process

    CN112646537A

  • Folding-resistant UV transfer film and production process thereof

    CN113547868A

  • Ultrahigh-temperature-resistant protective film adhesive and preparation method thereof

    CN115368852A

  • Degradable thermal-insulation rainbow film and preparation method thereof

    CN115464947A

Cited By

  • Biological synergistic method for improving fungal and bacterial disease control effect

    CN122478053A